UDCA Inhibits Hypoxic Hepatocellular Carcinoma Cell–Induced Angiogenesis Through Suppressing HIF-1α/VEGF/IL-8 Intercellular Signaling - Lin, Wanfu; Li, Shu; Meng, Yongbin; Huang, Guokai; Liang, Shufang; Du, Juan; Liu, Qun; Cheng, Binbin (Frontiers in Pharmacology, 2021)
Background: A hypoxic microenvironment may induce angiogenesis and promote the development of hepatocellular carcinoma (HCC). The aim of this study was to evaluate whether ursodeoxycholic acid (UDCA) may inhibit hypoxic HCC cell–induced angiogenesis and the possible mechanisms. Methods: Tube formation and matrigel plug angiogenesis assays were used to evaluate angiogenesis in vitro and in vivo, respectively. Real-time PCR, enzyme-linked immunosorbent assay, and Western blot were used to evaluate the mRNA and protein expressions of hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), and IL-8, respectively. Dual-luciferase reporter assay was applied to assess the reporter gene expression of hypoxia-response element (HRE). Results: UDCA antagonized hypoxic Huh 7 cell-induced tube formation of EA.hy 926 cells. In HCC cells, UDCA inhibited hypoxia-induced upregulation of VEGF and IL-8 both in mRNA and protein levels. UDCA also inhibited IL-8–induced angiogenesis in vitro and in vivo through suppressing IL-8–induced phosphorylation of ERK. The levels of HIF-1α mRNA and protein and HRE-driven luciferase activity in HCC cells were upregulated by hypoxia and were all inhibited by UDCA. The proteasome inhibitor MG132 antagonized the effect of UDCA on HIF-1α degradation. In hypoxic condition, the phosphorylation of ERK and AKT was obviously increased in HCC cells, which was suppressed by UDCA. Transfection of the HIF-1α overexpression plasmid reversed the effects of UDCA on hypoxic HCC cell–induced angiogenesis, HRE activity, and expressions of IL-8 and VEGF. Conclusions: Our results demonstrated that UDCA could inhibit hypoxic HCC cell–induced angiogenesis through suppressing HIF-1α/VEGF/IL-8–mediated intercellular signaling between HCC cells and endothelial cells.